2014
DOI: 10.2478/hukin-2014-0036
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Single Session of Whole-Body Vibration Training in Recreationally Active Men on the Excitability of the Central and Peripheral Nervous System

Abstract: Vibration training has become a popular method used in professional sports and recreation. In this study, we examined the effect of whole-body vibration training on the central nervous system and muscle excitability in a group of 28 active men. Subjects were assigned randomly to one of two experimental groups with different variables of vibrations. The chronaximetry method was used to evaluate the effect of a single session of whole-body vibration training on the excitability of the rectus femoris and brachior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…This demonstrates that utilizing WBV as a specific warm-up, may lead to acute increased neuromuscular performance (force and power) prior to an explosive bout of exercise (Cardinale & Bosco, 2003;Dabbs et al, 2010;Dabbs et al, 2011;Dabbs et al, 2012;Dallas et al, 2014;Marin et al, 2013;Rittweger et al, 2000;Ritzmann et al, 2013;Ronnestad et al, 2012). Conversely, the literature has also shown that WBV has failed to demonstrate significant increases in performance (Chmielewska et al, 2014;Rittweger et al, 2000;Ritzmann et al, 2013). Chmielewska (2014) demonstrated that WBV did not alter motor unit recruitment of the rectus femoris after exposure to either low-or high-frequency vibration during repeated squats.…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…This demonstrates that utilizing WBV as a specific warm-up, may lead to acute increased neuromuscular performance (force and power) prior to an explosive bout of exercise (Cardinale & Bosco, 2003;Dabbs et al, 2010;Dabbs et al, 2011;Dabbs et al, 2012;Dallas et al, 2014;Marin et al, 2013;Rittweger et al, 2000;Ritzmann et al, 2013;Ronnestad et al, 2012). Conversely, the literature has also shown that WBV has failed to demonstrate significant increases in performance (Chmielewska et al, 2014;Rittweger et al, 2000;Ritzmann et al, 2013). Chmielewska (2014) demonstrated that WBV did not alter motor unit recruitment of the rectus femoris after exposure to either low-or high-frequency vibration during repeated squats.…”
Section: Introductionmentioning
confidence: 90%
“…Improvements in power, developed from multiple training sessions, have been shown to enhance sport performance (Adams et al, 2009;Gerakaki et al, 2013;Haff et al, 2005;Kurt et al, 2014;Lamont et al, 2010). There are a number of traditional methods such as anaerobic and aerobic protocols that are utilized which lead to an increase in power production; however, athletes and coaches alike are continually looking for novel methods that are more efficient at IJKSS 3(4):31-39, 2015 32 improving performance (Cardinale & Bosco, 2003;Chmielewska et al, 2014;Dabbs et al, 2010;Dabbs et al, 2011;Dabbs et al, 2012;Dallas et al, 2014;Kurt et al, 2014;Lamont et al, 2010;Marin et al, 2013;Rittweger et al, 2000;Ritzmann et al, 2013;Ronnestad et al,2012). Traditionally, a warm-up is recommended prior to performing an exercise (Thompson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations